2019
DOI: 10.1039/c8gc03919d
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium chloride-Co(iii) complex immobilized on Fe3O4@SiO2 as a highly active bifunctional nanocatalyst for the copper-, phosphine-, and base-free Heck and Sonogashira reactions

Abstract: A green and efficient method has been developed for Heck and Sonogashira reactions by a magnetic Co(iii) bi-functional catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 58 publications
4
37
0
Order By: Relevance
“…The results showed that consecutive functionalization of the nanoparticles by silicate and chlorophyll groups did not change the phase and structure of the Fe 3 O 4 core, and no shifts were observed at peak angles (Figure 4c). [ 41,46 ] The four peaks appearing in 28.7°, 40.7°, 66.7°, and 50.4° corresponded to the crystalline phase of the chlorophyll decorated on the Fe 3 O 4 @SiO 2 nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that consecutive functionalization of the nanoparticles by silicate and chlorophyll groups did not change the phase and structure of the Fe 3 O 4 core, and no shifts were observed at peak angles (Figure 4c). [ 41,46 ] The four peaks appearing in 28.7°, 40.7°, 66.7°, and 50.4° corresponded to the crystalline phase of the chlorophyll decorated on the Fe 3 O 4 @SiO 2 nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Fe 3 O 4 @SiO 2 NPs were prepared according to a co‐precipitation method followed by coating with silica shell that was previously reported elsewhere. [ 40,41 ]…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, there are few composites which have the constitutes that chemically interact with each other. Graphene oxide, polyethylene glycol, polyethyleneimine, allyl calixarene, and polymerized cobalt(III) complex are involved in the chemical interaction with FSs during the formation of FS composites . The non‐FSs have formed the composites with the polymers containing significant functional groups.…”
Section: Composites As Fssmentioning
confidence: 99%
“…While iron(III) FS catalyst is useful in the cross‐coupling reaction between olefins and aryl iodides, nickel(II) FS catalyst promotes the Kumada‐Corriu reaction . Cobalt(III) FS is reported to be a catalyst for Heck‐Mizoroki and Sonogashira couplings . Of note, the first row transition metal FS catalysts are seen as the affordable substitutes for the costly noble palladium catalysts in C−C coupling reactions…”
Section: Applications and Advantages Of Fs‐based Catalystsmentioning
confidence: 99%
“…Magnetically recoverable catalysts can be utilized in a wide range of reactions. Magnetic nanoparticle surfaces can be tailored for a specific application by designing a specific surface activation, thus resulting in versatile carriers [36][37][38][39][40][41] . Developments in the immobilization of enzymes can improve the stability and activity of enzymes and expand the range of conditions in which the enzymes can be used by significantly increasing the total turnover number and significantly improving the overall process efficiency 42 .…”
mentioning
confidence: 99%